PAUL'S CONCEPT OF SALVATION - CULMINATION OF AN EVOLUTIONARY PROCESS - Nürnberger, Klaus (Scriptura, 2002)
This essay is an attempt to demonstrate that Paul's concept of salvation is the culmination of a long evolutionary history in biblical times. The nature of the "law" moved from an unspecified kind of faithfulness (zedaqah), through rather rigid and increasingly elaborate apodictic, casuistic and ritual formulations, to common wisdom and finally an open kind of motivational renewal "in the Spirit". The contents of the law changed substantially from rather authoritarian to increasingly participatory forms. The relationship between God and humans moved from a gratuitous relation between a superior and a subordinate, through the conditionality of the covenant to God's unconditional but transforming acceptance of the unacceptable in the theology of Paul. God's redeeming acceptance into his fellowship restores the relationship of sinners with God and brings about their transformation. Paul's soteriology is characterised most profoundly by the eschatological transition of the human being from "flesh" (or this age) to "Spirit" (or the age to come), anticipated in faith through the power of the Spirit, rather than by the doctrine of justification. Paul's disciples were not able to maintain these lofty thoughts, nor was Paul himself. The essay closes with a few instances which demonstrate the decisive and pervasive relevance of the distinction between conditional and unconditional acceptance in modern society.